Probability and Contracts. About Roberto Torretti’s Pragmatism - Teira, David (Revista de Humanidades de Valparaíso, 2016)
I want to expand the pragmatist view of probability advocated by Roberto Torretti, drawing on the propensity approach. In the first part, I will show how the concept of mathematical expectation originally formalized an Aristotelian principle of justice. In the second half, I will present the game-theoretic approach to probability developed by Shafer and Vovk, showing how it allows us to interpret the original normativity of mathematical expectations. I will finally discuss how this latter view contributes to a pragmatist understanding of probability, as Torretti advocates, although with broader foundations than the physical symmetries of standard propensities.